EFFECT OF CARROT FLOUR (Daucus carota) TO INCREASE GROWTH AND COLOR BRIGHTNESS IN LEMON CICHLID FISH (Labidochromis caeruleus) - Octaviani, Dheamita Ayu; Armando, Eric; Jaelani, Abdul Qadir (Asian Journal of Aquatic Sciences, 2022)
Ornamental fish is one of the main merchandise from the fisheries sector whose ability can generate income for the state and create income that can help the community's economy, especially those who are engaged in fisheries or cultivators. The most effective and dominant type of carotenoids for coloring fish is carotenoids derived from carrot flour because it is a natural source of beta carotene which can improve the quality and color brightness of ornamental fish such as lemon fish. The research design used a completely randomized design (CRD) with four treatments (carrot flour 0%, 5%, 10% and 15%) and three replications. The feed was tested on lemon cichlid fish measuring 3.7 - 4 cm and weighing 0.8 - 1 g which were kept in a 10 L jar. Parameters observed were growth rate, absolute weight, absolute length growth rate, survival rate, water quality and color increase in lemon fish. The results showed that the addition of 15% carrot flour had an effect on the color 9% brightness of lemon fish (Labidochromis caeruleus). The results showed that the addition of carrot flour for growth and color improvement was in the 15% carrot flour treatment, the absolute weight growth value was 0.73 g/fish, length 0.56 cm/fish, survival rate was 96.6%. The addition of carrot flour to the growth and color improvement can be concluded that a dose of 15% affects growth and can increase the color of lemon fish.